Perlindungan Hukum Terhadap Hak Pasien Pengguna Kartu BPJS Dalam Pelayanan Kesehatan - Kurniawan, Heri; Kusuma, Rahmawati (Fakultas Hukum Universitas Mataram, 2024)
The purpose of this research is to determine the legal protection for the rights of patients using BPJS cards in health services and to understand the legal implications in case of violations of the rights of patients using BPJS cards in health services. The type of research used is prescriptive research. The research employs a legislative approach and a conceptual approach, historical approach. The data collection of legal materials technique used involves a literature study conducted through document analysis, research findings, work outcomes, and legal regulations, employing qualitative analysis methods. The results of the study indicate that legal protection for the rights of BPJS participant patients has been regulated in several laws, namely the Consumer Protection Law, the Medical Practice Law, the Health Law, and the Hospital Law. Thus, BPJS participants can claim compensation from hospitals as health service providers and/or health workers. If hospitals and medical personnel engage in discriminatory actions, the hospital as a health service provider or health worker can also be subject to criminal sanctions as regulated in Article 190 of Law Number 36 of 2009 concerning Health. Meanwhile, the accountability of hospitals and doctors who do not provide health services as determined by three criteria of responsibility: civil law, administrative law, and criminal law.